Pelatihan Pembuatan Media Pembelajaran Pop Up di TPQ At Taqwa Tembelang Jombang - Nurul Afidah; Iin Baroroh Ma'arif; Ulfa Wulan Agustina (IAI Darussalam, 2022)
ABSTRACT: In this training, the use of Pop Up in learning was introduced along with its benefits to 45 participants in TPQ At-Taqwa Bedahlawak Jombang. The steps conducted in this activity covered, socialization, training, monitoring, and evaluation. In socialization the instructor explained the benefits of Pop Up and how to design it. After identifying the benefits, in training phase, the participant that was divided in to some group were also asked to construct the pop up. During constructing process, the whole participants were quite excited. Then, on monitoring and evaluation, it was found that there some positive impacts obtained after conducting this activity. The students were very enthusiast toward the instructional media, the teacher had additional instructional media, and the parents identified the benefits of Pop Up.